CHRONIC LYMPHOCYTIC LEUKEMIA ARISING IN PATIENT WITH HODGKIN LYMPHOMA TREATED WITH PERIPHERAL BLOOD STEM CELL TRANSPLANTATION -CASE REPORT - Trajkova, Sanja; Pivkova-Veljanovska, Aleksandra; Popova-Labacevska, Marija; Ivanovski, Martin; Krstevska-Balkanov, Svetlana; Ridova, Nevenka; Stojanovska, Simona; Panovska-Stavridis, Irina (Journal of Morphological Sciences, 2022)
Post-transplant lymphoproliferative disorders (PTLDs) are lymphoid or plasmacytic proliferations that develop as a consequence of immunosuppression in a recipient of a solid organ, bone marrow or stem cell allograft. The development of PTLDs is usually associated with Epstein-Barr virus (EBV) and the disorder is also termed EBV-associated lymphoproliferative disorder (LPD). The development of PTLD is a rare complication in autologous bone marrow/peripheral blood stem cell transplantation. In the present study, we report a case of   LPD which developed following autologous peripheral blood stem cell transplantation for relapsing Hodgkin's lymphoma. Keywords: CLL, post-transplant lymphoproliferative disorders, Covid 19.